2008
DOI: 10.1029/2008jd010282
|View full text |Cite
|
Sign up to set email alerts
|

Wine ethanol 14C as a tracer for fossil fuel CO2 emissions in Europe: Measurements and model comparison

Abstract: [1] 14 C (radiocarbon) in atmospheric CO 2 is the most direct tracer for the presence of fossil-fuel-derived CO 2 (CO 2 -ff). We demonstrate the 14 C measurement of wine ethanol as a way to determine the relative regional atmospheric CO 2 -ff concentration compared to a background site (''regional CO 2 -ff excess'') for specific harvest years. The carbon in wine ethanol is directly back traceable to the atmospheric CO 2 that the plants assimilate. An important advantage of using wine is that the atmosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 47 publications
3
43
0
Order By: Relevance
“…This implies that the seasonal effect is much less sensitive to CO 2 fossil sources and sinks (photosynthesis) in summer than in winter. This effect is called the "seasonal rectifier effect" (Denning et al 1999;Palstra et al 2008). A comparison with the temperature curve shows that a small fossil carbon asymmetry between the spring and autumn parts seems to be visible, although the temperatures are similar.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the seasonal effect is much less sensitive to CO 2 fossil sources and sinks (photosynthesis) in summer than in winter. This effect is called the "seasonal rectifier effect" (Denning et al 1999;Palstra et al 2008). A comparison with the temperature curve shows that a small fossil carbon asymmetry between the spring and autumn parts seems to be visible, although the temperatures are similar.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that plant material records the broad spatial patterns of 14 CO 2 in the modern atmosphere, using corn leaves (Hsueh et al, 2007;Riley et al, 2008), wine ethanol (Palstra et al, 2008), and rice grains (Shibata et al, 2005). Several of these studies compared the observations with model predictions, and achieved reasonable agreement at the continental and regional scales, mostly reflecting the spatial pattern of CO 2 ff emissions.…”
Section: Grass Samplesmentioning
confidence: 99%
“…The 14 C content of CO 2 is also maintained in carbon assimilated by plants so that the average 14 C of the assimilated CO 2 , and hence the overlying atmosphere at the time of uptake, can be determined from the 14 C content of plant materials (e.g. Hsueh et al, 2007;Palstra et al, 2008). CO 2 assimilation rates vary with local climatic weather conditions, plant type, and plant growth phase, meaning that a complex weighting function may be needed to describe the averaging period (Bozhinova et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to these, at the other end of the time spectrum is the use of plants to sample 14 C / C ratios in the atmosphere through their photosynthetic fixation of atmospheric CO 2 . Depending on the species these integrate over sampling windows of a full growing season (annual crops, fruits -Shibata et al, 2005;Hsueh et al, 2007;Palstra et al, 2008;Riley et al, 2008;Wang et al, 2013) or longer (trees, tree-rings -Suess, 1955;Stuiver and Quay, 1981;Wang et al, 2012). …”
Section: Bozhinova Et Al: Modeling 14 Co 2 For Western Europementioning
confidence: 99%
“…(1) and (2), following the methodology used by Levin et al (2003), Turnbull et al (2006), Hsueh et al (2007), Palstra et al (2008) and described thoroughly in Turnbull et al (2009b). Here the x and CO 2x (or 14 CO 2x ) indicate the 14 CO 2 signature of CO 2 (or 14 CO 2 ) mole fractions of particular origin, expressed in the index as follows: obs -observed at location, bg -background, fffossil fuels, p -photosynthetic uptake, r -ecosystem respiration, o -ocean, n -nuclear and s -stratospheric.…”
Section: The Regional Atmospheric Co 2 and 14 Co 2 Budgetmentioning
confidence: 99%